APPLICATION OF ADMINISTRATIVE COSTS COURSE COURSE IN ENGLISH INSTITUTE OF BAHASA CAMBRIDGE SCHOOL - Sarita Anggiaty; Yuce Yuliani, SKom, MMSI Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This explains the scientific writing about the design of the course fee administrativeapplications using Visual Basic 6.0 programming language.In this study also used a database program using the Visual Data Manager (VisData) thathas been integrated in Visual Basic 6.0 program. Table in which data from fourparticipants, costs, employee and Payment.In the end application program administrative costs of these courses will be applied to theInstitute of English Courses Cambridge School of Home branch Pamulang to ease thefinancial administration activities at the venue.